Career success schemas and their contextual embeddedness: A comparative configurational perspective. (29th November 2018) - Kaše, Robert; Dries, Nicky; Briscoe, Jon P.; Cotton, Richard D.; Apospori, Eleni; Bagdadli, Silvia; Çakmak‐Otluoğlu, K. Övgü; Chudzikowski, Katharina; Dysvik, Anders; Gianecchini, Martina; Saxena, Richa; Shen, Yan; et al.
Abstract: We introduce career success schemas as critical for understanding how people in different contexts perceive and understand career success. Using a comparative configurational approach, we show, in a study of 13 countries, that two structural characteristics of career success schemas—complexity and convergence—differ across country contexts and are embedded in specific configurations of institutional factors. Adopting complexity and convergence as primary dimensions, we propose a taxonomy of career success schemas at the country level. Based on this taxonomy, we contribute to the understanding of subjective career success across countries, discuss the importance of schemas for organisational career systems in multinational enterprises, and propose specific guidelines for future comparative careers research.